ZYMOGRAPHY OF EXTRACELLULAR PROTEASES IN Bacillus subtilis - Kodama, Takeko; Endo, Keiji; Ara, Katsutoshi; Ozaki, Katsuya; Sekiguchi, Junichi (International Journal of Biosciences and Biotechnology; Vol 1 No 2 (2013), 2013)
In Bacillus subtilis, AprE, Bpr, Epr, Mpr, NprB, NprE, Vpr and WprA have been identifi ed as extracellularproteases. We determined protease activities from the culture supernatant of Bacillus subtilis using a 1Dzymogram gel containing gelatin. The highest protease activities were found at the late stationary phase ofa 75-h culture. To distinguish the proteases, the zymogram patt ern of the wild type was compared with theprotease-defi cient mutants (aprE, bpr, epr, mpr, nprB, nprE, vpr and wprA). Activities of AprE, Bpr, Mpr, andVpr were estimated by gelatin zymography. In addition, for the aprE mutant, the zymogram profi le of Bprwas very diff erent from that of the wild type. This suggested that AprE is involved in processing the Bprprotein.
Keywords: protease, zymography, gelatin, Bacillus subtilis